Recontriving culture/nature dualism: An ecofeminist reading of selected Terry Pratchett’s Witches series - Soon, Cai En (2023)
This study uses Warren’s (2000) Oppressive Conceptual Framework in Terry Pratchett’s Equal Rites, Wyrd Sisters and Witches Abroad to debunk the ageold notion that man is to culture as woman is to nature. In these fantasy novels where magic is brought to life, the witches do not conform to stereotypes of villainous witches which questions the binary oppositions of culture and nature as they do not fit into one disjunct only. All five concepts from Warren’s framework – value dualism, value hierarchy, power over power, conception and practice of privilege and logic of domination – are used to analyse the witches’ role in Pratchett’s Discworld. The concept of value dualism and value hierarchy are similar because one element is valued over the other, with difference only in that value dualism is between two disjuncts with one valued over the other while value hierarchy is when greater value is placed on higher rank. Power over power and conception and practice of privileges denotes one disjunct having more power and privilege over another disjunct which is seen in the power and privilege exercise by the witches. These concepts contribute to the logic of domination – a justification to dominate. In all three books, the depiction of witches and witchcraft and their association with nature while maintaining a relationship with culture shows that culture and nature are neither truly separated nor truly together because the witches are both culture and nature. They embody nature and maintain the balance between culture and nature to ensure that Discworld does not fall into chaos. The logic of domination crumble in Discworld because culture’s existence relies on nature and vice versa similarly neither can men exist without women and vice versa. Therefore, it is neither culture over nature nor nature over culture, it is a balance between culture and nature on the same plane of existence and reliance.